Hepatoprotective effect of Phellinus linteus mycelia polysaccharide (PL-N1) against acetaminophen-induced liver injury in mouse - Chen, Chen (2020)
Edible and medicinal fungi are one of the major sources for extraction and identification of polysaccharides, which are important biological response modifiers with notable antitumor, hepatoprotective effect and other pharmacological activities. This study aimed to evaluate the hepatoprotective effect of isolated Phellinus linteus polysaccharide (PL-N1) against acetaminophen (APAP) induced liver injury in mice. Mice were treated intragastrical with PL-N1 (10, 50 and 100 mg/kg) and APAP (300 mg/kg) injection. APAP alone caused increased serum aminotransferase levels and changes in hepatic histopathology, promoted oxidative stress by increasing lipid peroxidation and decreasing anti-oxidant enzyme activities, leading to hepatocellular necrosis and reduced liver function. PL-N1 decreased cytochrome P450 2E1 (CYP2E1) expression and hepatic release of cytokines to enhance the level of phase II enzymes. Also, PL-N1 obviously accelerates the metabolism of APAP in the rat model. Molecular docking analysis revealed the α-d-glucopyranosyl exhibit maximum interaction (-8.099) against CYP2E1 as comparably less than standard drug silibinin (-13.767). PL-N1 could be a promising natural substance for ameliorating acute APAP-induced oxidative stress and hepatic injury.